Investigating the optical and electronic properties of halide perovskite inspired antimony compounds - Padinhare Cholakkal Harikesh (Nanyang Technological University, 2020)
This thesis investigates the optical and electronic properties of ns2 electron containing Antimony compounds. The study is focused on two material systems - A3Sb2I9 and NaSbS2. The work reveals the role of A cation in templating layered A3Sb2I9 structures and the effect of Atomic mass of Metal cation in affecting defects in these compounds. The partial substitution of Sb with Bi was shown to tune the carriers from p to n type by changing the defects in the material. This work also reported, for the first time, switchable Photovoltaic effect in Lead free perovskites and utilized ionic-electronic coupling in NaSbS2 for potential applications in neuromorphic devices.